Organ‐specific autoimmune markers in adult patients with type 1 diabetes mellitus. Issue 12 (22nd September 2021) - Bilginer, Muhammet Cuneyt; Faki, Sevgul; Ozdemir, Didem; Baser, Husniye; Polat, Burcak; Bestepe, Nagihan; Topaloglu, Oya; Ersoy, Reyhan; Cakir, Bekir
Abstract: Aim: We aimed to investigate the presence of thyroid, celiac disease (CD) and anti‐parietal cell antibodies (APCA) in adult type 1 diabetes (T1DM) patients. Methods: Data of 287 T1DM patients >16 years old were reviewed retrospectively. Thyroid disease related, CD related antibodies and APCA were evaluated. Patients were divided into early onset (<30 years old) and late‐onset (≥30 years old) TIDM, and ≤10 years, 11‐20 years and >20 years according to disease duration. Results: There were 142 (49.5%) female and 145 (50.5%) male patients. The median age at diagnosis and disease duration were 21 (2‐53) and 6.91 (0‐50.8) years, respectively. Antibody positivity rates were anti‐glutamic acid decarboxylase (anti‐GAD) 72.8%, anti‐insulin 9.1%, anti‐islet cell 25.7%, antithyroid peroxidase (anti‐TPO) 34.8%, anti‐thyroglobulin 19.9%, anti‐endomysial IgA (EMA‐IgA) 7.6%, anti‐gliadin IgA (AGA‐IgA), 12.2%, AGA‐IgG 13.0%, tissue transglutaminase IgA 7.1% and APCA 14.4%. One hundred twenty‐eight (44.6%) patients had at least one non‐diabetes autoantibody. Thyroid autoantibodies and dysfunction were significantly higher in women than men. Anti‐TPO positivity was higher in the late‐onset group ( P = .044). Anti‐GAD level was correlated with thyroid related antibody positivity in male patients with positive anti‐GAD ( r : .340, P : .006). The positivity of EMA‐IgA and AGA‐IgA was higher in patients with disease duration >20 years ( P = .017 and .039, respectively). Conclusion: Almost half of the adult T1DM patients were positive for at least one non‐diabetic antibody. It is important to investigate thyroid autoimmunity in patients diagnosed with T1DM at any age, including advanced age. CD associated antibody positivity increases with disease duration, suggesting that they should be re‐evaluated at clinical suspicion, even if prior tests were negative.